STRATEGIES USED BY INSTRUCTORS TO REDUCE STUDENTS' SPEAKING ANXIETY: الاستراتيجيات التي يستخدمها المعلمون لتقليل قلق الطلاب من التحدث (مجلة ديالى للبحوث الانسانية, 2022)
The issue of anxiety in second or foreign language learning has been widely studied because it has  significant impact on the learners progress and performance. This study is a case study which aimed at measuring the speaking anxiety level of undergraduate students at college of Basic Education and to detect instructors' use of certain strategies to reduce their students' speaking anxiety. The study hypothesizes that the frequent use of certain interventions by college instructors is supposed to reduce students speaking anxiety. For this purpose, 40 fourth year students and 20 instructors at college of Basic Education were taken as the subjects. Two instruments are used to achieve the studies goal which are; Foreign Language Classroom Anxiety Scale (FLCAS) designed by Horwitz et al. (1986) to assess the degree of the students' anxiety and a Questionnaire based on Tsiplakide's  & Keramida  (2009) research where many classroom interventions are used to reduce foreign language speaking anxiety. The aim is to detect instructors' frequent use of such strategies to reduce students' speaking anxiety level. The results of (FLCAS) showed high speaking anxiety level with the mean(3.49) of the 40 students , while the questionnaire also showed a frequent use of such strategies with the  mean (3. 94) which indicates a positive correlation between the two (R= 0.1875) .A negative correlation was hypothesized to be found since the frequent use of strategies should lead to anxiety reduction.